2014
DOI: 10.1097/ijg.0b013e31826981c9
|View full text |Cite
|
Sign up to set email alerts
|

Early Efficacy and Complications of Releasable Sutures for Trabeculectomy in Primary Angle-closure Glaucoma

Abstract: The technique of releasable sutures for trabeculectomy used in this study did not demonstrate significant advantages over standard trabeculectomy. Releasable sutures were associated with some decrease in visual acuity and increase in postoperative complaints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
0
8
1
2
Order By: Relevance
“…57,68,69 We also observed that daytime fluctuations in PACG after trabeculectomy, 3.8 ± 2.1 mm Hg 70 was lower than that reported after LPI, 5.44 ± 2.4 mm Hg. 71 Increased use of trabeculectomy may be suggested in the management of both PACG and POAG.…”
Section: Complications Of Initial Lpi and Trabeculectomycontrasting
confidence: 72%
See 1 more Smart Citation
“…57,68,69 We also observed that daytime fluctuations in PACG after trabeculectomy, 3.8 ± 2.1 mm Hg 70 was lower than that reported after LPI, 5.44 ± 2.4 mm Hg. 71 Increased use of trabeculectomy may be suggested in the management of both PACG and POAG.…”
Section: Complications Of Initial Lpi and Trabeculectomycontrasting
confidence: 72%
“…60,61 In addition, the surgery impairs visual acuity during the early phase in about 20% of the patients. 57,62 PRIMARY TRABECULECTOMY There are limited data for primary trabeculectomy in PACG compared with LPI, but there are some welldesigned studies that reported the results of trabeculectomy as an initial treatment in POAG patients. We can only attempt to extrapolate this to PACG.…”
Section: Complications Of Initial Lpi and Trabeculectomymentioning
confidence: 98%
“…Although this procedure is very effective in reducing intraocular pressure (IOP) in the short term, surgical failure has often been observed over time[5, 6]. Additionally, trabeculectomy is associated with a high incidence of early and late postoperative complications[710], therefore, an alternative to trabeculectomy for treating glaucoma is urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…En relación con el uso de suturas liberables en la trabeculectomía de ojos con GCAP, Liang et al realizaron un estudio prospectivo y aleatorizado incluyendo a 87 pacientes en el grupo de trabeculectomía estándar y 88 en el grupo de suturas liberables (dos permanentes y dos liberables) 89 . La eficacia hipotensora ocular a los 3 meses fue similar con ambos procedimientos.…”
Section: Tratamiento Quirúrgicounclassified
“…La eficacia hipotensora ocular a los 3 meses fue similar con ambos procedimientos. La hipotonía transitoria fue observada más frecuentemente en el grupo de suturas fijas (20,4% vs 9,1%), no encontrándose diferencias significativas en la incidencia del resto de complicaciones 89 .…”
Section: Tratamiento Quirúrgicounclassified